One-Year Readmission and Emergency Department Presentation After an Epilepsy-Related Admission in People with Intellectual Disability: A Registry-Linkage Study - Liao, Peiwen (International Journal of Population Data Science, 2020)
Introduction Intellectual disability (ID) is a neurodevelopmental condition that affects approximately 1-2% of the population, and epilepsy is a common comorbidity in people with ID. Although hospital admission for epilepsy is also common, little is known about the impact of ID on healthcare use following an epilepsy admission. Objectives and Approach Using linked administrative health datasets that included hospital admissions and disability service data, we aimed to examine whether the presence of ID led to greater or lesser use of healthcare services following an epilepsy admission, as represented by all-cause unplanned readmissions and emergency department (ED) presentations. Comparing the rate of readmissions and ED presentations within 30, 90 and 365 days of the first epilepsy admission during the study period, the effect of ID was assessed using Poisson regression. Results A total of 18,987 patients had an epilepsy admission between 2005 and 2014, and of these, 3,256 (17.1%) had ID. Compared to patients without ID, patients with ID had a higher risk of unplanned readmissions within each follow-up period (adjusted incidence rate ratio (IRR) with 95% CI: 30 days: 1.48 (1.34, 1.65); 90 days: 1.42 (1.31, 1.54); 365 days: 1.49 (1.40, 1.59)). Differences were also found in the reasons for readmission, including more readmissions for neurological disorders. Similarly, the ED presentation risk was elevated in patients with ID (adjusted IRR: 30 days: 1.34 (1.23, 1.46); 90 days: 1.33 (1.24, 1.42); 365 days: 1.38 (1.30, 1.46)). Conclusion / Implications In patients with epilepsy, the presence of ID appears to increase the chance of a readmission or ED presentation following a hospital admission for epilepsy, with the reasons for readmission also potentially different. This suggests the potential for improvements in post-admission screening and management.